(3eLeY GdSQhQ heWdY GdTehS hGdHOhQ aj ePGgH GdbQGA GdCQHYI YTQs - (3GHf GdbHGbHj , eMeO Hf Ndjd Hf CHj HcQ Hf eMeO, TeS GdOjf , CHh YHO Gddg,J (B849 (3g` s
(3ChdgG (B:s
(3jbhd QGLi Gddg Pi GdehGgH eMeO GdTgjQ HGdbHGbH ef HYO MeO Gddg hGdUdGI Ydi GdfHi TGaY GdYUGI SHMGf ef ddYeGA TQaG HeG dge ef GdYdhe YQaG s
(3BNQgG (B:s
(3hCMeO Gddg eUdjkG Ydi ef QMeI ddYGdejf CQSdG hBdg GdZQ GdcQGe GdTQaG hUMHg GdPjf fGdhG GdTQaG cedJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdGeJgG HGdMeQI hGdVHW HGdMeQI CjVkGs
(3aQZ fGXegG efgG ai ZQI SfI NGA dGe Cda s
(3hYOO CHjGJgG (B" (3ZjK (B" s
(3efXheI GdbQGAGJ Ydi ePgH GdbQGA GdCQHYI YTQ s
Keywords: (3GdbQGAGJ hGdJLhjOs